2011
DOI: 10.1007/s00464-011-1758-2
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision laparoscopic colectomy for malignant disease

Abstract: SIL-C can be used safely in selected colon cancer patients with no difference in blood loss, OR time, or lymph node retrieval. SIL-C patients may have a shorter LOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…The literature search identified one randomized contro lled trial and 13 cased-matched control or comparative studies [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . In total, 1559 colorectal resections were included, 589 by SILC and 970 by CLC.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified one randomized contro lled trial and 13 cased-matched control or comparative studies [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . In total, 1559 colorectal resections were included, 589 by SILC and 970 by CLC.…”
Section: Resultsmentioning
confidence: 99%
“…All margins were free of cancer in these series. In 18 studies with available data, the range of number of removed lymph nodes for malignant cases and potential malignant diseases was 12–24.6 (Table 4) [19, 20, 2225, 27, 28, 3039]. …”
Section: Resultsmentioning
confidence: 99%
“…A total of 9 comparative studies [19, 22, 24, 27, 30, 31, 33, 35, 36] including 6 case-matched studies [22, 24, 27, 31, 33, 36] between SILC and other minimally invasive procedures are summarized in Tables 5 and 6. Ramos-Valadez et al, in their case-matched series (SILC versus LAC group), reported that mean estimated blood loss was significantly lower for the SILC group ( n = 20) compared to the LAC group ( n = 20) (58 versus 99 mL, P < 0.007) [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A cohort study of 73 patients by McNally et al 14 in 2011 concluded that SILC can be used safely in selected colon cancer patients with no difference in blood loss, operating room time, or lymph node retrieval. A similar study by Egi et al 15 comparing surgical outcomes for colon cancer showed no significant differences regarding the perioperative and oncologic results between SILC and MLC.…”
Section: Silc For Malignancymentioning
confidence: 99%